Effect of Mother Trees and Cuttings Material Position on the Stool Plants to Shorea leprosula Shoot Cuttings Growth - Mashudi (Jurnal Penelitian Kehutanan Wallacea, 2019)
Vegetative propagation plays an important role to support Shorea leprosula’sclonal forestry development. This study aimed to determine the effect of mother trees and cuttings material position of S. leprosula shoot cuttings grow that 4 months of age. Complete Randomized Design (CRD) was used as the experimental design, which consists of two factors, i.e. cuttings material position (4 level) and mother trees (10 mother trees). The results showed that the interaction between mother trees and cuttings material position significantly affected the growth of height and the number of the leaf. The best interactions in height of growth values ranged from 7.83 to 8.83 cm and the best number of leaves ranged from 3.6 to 4.5 sheets. The single factor of the cuttings material position and mother trees significantly affected the rooting percentage, the number of the root, and the length of the root. The cuttings material position at 20 cm, 40 cm, and 60 cm found to be the best rooting percentage (84 to 88%), the cuttings material position at 40 cm and 60 cm found to be the best number of the root (4.04 to 4.43 pieces) and the best length of the root (10.23 to10.93 cm).